KAJIAN PRINSIP NON-INTERVENSI ASEAN DALAM KERANGKA ORGANISASI EKONOMI INTERNASIONAL - Setiawan Wicaksono (Fakultas Hukum Universitas Riau, 2018)
ASEAN as an international organisation and economoc regional integration has wider meaning than just an economic integration, its also hold social and integration between its members. Consequences are, ecah members have to realize to solve problems together to reach the AEC and ASEAN goals itself. This research use normative method with conceptual approach and teortical approach to find out why the principle and goals in ASEAN didn’t run corectly. Author find outs that there are several obstacles in ASEAN which are: there is still lack of commitment in ASEAN members, ASEAN ideologist which greatly adore the non-intervention principle, and ASEAN weakness in settling conflicts.